Hubungan Kombinasi Pilates Exercise Dan Aromaterapi Lavender Terhadap Nyeri Haid Pada Remaja Putri - Sriwidyastuti Sriwidyastuti; Susilawati Susilawati; Ermawati Ermawati; Sumarni Sumarni; Musdalifah Musdalifah (Jurnal Kesehatan Marendeng, 2026)
Abstract. Menstrual pain (dysmenorrhea) is a common complaint among adolescent girls and can disrupt daily activities. This study aims to determine the relationship between the combination of Pilates exercise and lavender aromatherapy on menstrual pain in adolescent girls at the Faculty of Science and Health, Andi Sudirman University in 2025. This study used a one-group pre-test and post-test design with a sample of 37 respondents selected using a purposive sampling technique. The combined intervention of Pilates exercise and lavender aromatherapy inhalation was carried out for 30 minutes. Data were collected using a Numerical Rating Scale (NRS) questionnaire and analyzed using a chi-square test. The results showed a decrease in menstrual pain intensity after the intervention, with a p-value of 0.000 (p<0.05). The conclusion of this study is that there is a significant relationship between the combination of Pilates exercise and lavender aromatherapy on reducing menstrual pain in adolescents. This therapy can be used as an alternative non-pharmacological treatment to reduce dysmenorrhea